2019
DOI: 10.1080/13621718.2019.1706259
|View full text |Cite
|
Sign up to set email alerts
|

Improving mechanical properties of friction-stir-spot-welded advanced ultra-high-strength steel with additional water cooling

Abstract: 1.2 mm thick DP1180 advanced ultra-high-strength steel were successfully friction stir spot welded (FSSWed) with additional water cooling. No hook defect and obvious keyhole were observed in the spot joints when using a specially designed WC-Co tool. Softening of the heataffected zone was substantially suppressed and the lap shear strength of the joints was obviously enhanced via water cooling. The enhanced strength of water-cooled joints was attributed to the grain refinement, the formation of the untempered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The total generated heat during UFSW/FSW is dependent on the many mechanical parameters [ 61 , 62 , 63 ]. The used term of ¨heat production ratio¨ here refers to the ratio of the total heat generated by each part of the tool in the both the regular and underwater-FSW cases [ 32 , 64 ]. The heat production rate in all parts of the tool depends on the contact area of tool parts with the base metal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total generated heat during UFSW/FSW is dependent on the many mechanical parameters [ 61 , 62 , 63 ]. The used term of ¨heat production ratio¨ here refers to the ratio of the total heat generated by each part of the tool in the both the regular and underwater-FSW cases [ 32 , 64 ]. The heat production rate in all parts of the tool depends on the contact area of tool parts with the base metal.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the FSW case, the UFSW stir zone appears to be more homogeneous; meanwhile, no other major defects were detected in either case. Wang et al improved final properties of friction stir spot welding of advanced ultra-high-strength steel with additional water cooling [ 32 ]. According to their report, the mechanical properties of water-cooled welds were significantly improved, and the underwater cooling condition improves surface materials flow.…”
Section: Introductionmentioning
confidence: 99%
“…As the distance from the center increases, the hardness diminishes in proportion to the reduction of deformation, and in TMAZ, it is 2.5 times that of the BM. By adding the number of passes, the possibility of partial tempering of the martensite structure rises, and with recrystallization and grain growth, the hardness decreases [42]. As a result, in the P3 sample, the hardness of the SZ and the TMAZ reaches 767 and 469 HV, respectively.…”
Section: Microhardnessmentioning
confidence: 99%
“…Santella et al [22] revealed the effects of shoulder geometries on the joint performance of different AHSS. Wang et al [21] adopted water cooling during FSSW to improve the joint properties of DP1180 steel. However, up to now, the interface welding mechanism of AHSS, which CONTACT Hidetoshi Fujii fujii@jwri.osaka-u.ac.jp Joining and Welding Research Institute, Osaka University, 11-1 Mihogaoka, Ibaraki, Osaka, Japan Supplemental data for this article can be accessed here.…”
Section: Introductionmentioning
confidence: 99%